Características clínico-epidemiológicas, histomorfológicas e histoquímicas da esporotricose felina - Bazzi, Talissa (2015)
Sporotricosis is an acute or subacute mycotic infection caused by the Sporothrix complex species. The disease was already described in humans and in several animal species, mostly in cats, horses and dogs. Based on several outbreak reports in the literature, the species more predominant in cats of the Southeast and South regions of Brazil is S. brasiliensis. The transmission to humans include the occupational and the zoonotic forms. The presentation form more often seen in cats is multiple skin and mucosal lesions. The diagnostic methods include the isolation and identification of the agente in culture, the histopathology, the cytology, the intradermal sporotrichin test, the immunohistochemistry technique, and the polymerase chain reaction (PCR). The histopathological diagnosis is based on the morphological characteristics of the fungus and the respective inflammatory reaction. The main objectives of this retrospective study were to characterize the histomorphological and histochemical aspects of sporotrichosis in 10 cats, and also to evaluate epidemiological and clinical aspects, and gross findings obtained from the biopsy and necropsy protocols of the archives of the Laboratório de Patologia Veterinária of the Universidade Federal de Santa Maria. The disease affected mostly male mongrel cats, and was mostly observed in the cutaneous disseminated form. Gross lesions were characterized by cutaneous nodules (ulcerated or not) and by ulcerated masses or plaques. By histopathology, there were a relationship between the fungal load and two patterns of inflammatory response. The first pattern was characterized by high fungal load, and most yeasts were inside of numerous macrophages with abundant, many times vacuolated cytoplasm. The amount of neutrophils ranged from mild to moderate in this pattern. The second pattern was characterized by numerous epiteliod cells and many neutrophils. The fungal load was low and most yeasts were observed in the extracellular space. The yeasts were round, oval or cigar-shaped. Several histochemical techniques, such as Grocott s silver stain, periodic Schiff acid, and Alcian blue were utilized and they made it easier to visualize, to characterize the morphology, and to quantify the organisms. The Giemsa stain allowed visualizing the agent, but it not allowed to sharply highlight them from other intralesional components. Organisms were negative for melanin granules through the Fontana-Masson stain in all cases. The histomorphological and histochemical study allowed demonstrating determinant fungal characteristics to the establishment of the diagnosis by means of this diagnostic tool.